The Participatory Processes in Public Policy-Making: A Scoping Review - Teddy Moysan; Francisco Ródenas-Rigla (Societies)
The topic of participatory processes in public policy-making is becoming increasingly common, yet their quality remains disputed. There is as yet no reproducible quantitative assessment method that can be generalized to all such processes. This article proposes a scoping review, guided by the PRISMA research protocol, to identify key concepts linked with the democratic quality of participatory processes. The key concepts which appear are accountability, comprehensiveness, influence, results, deliberation, inclusiveness, representativeness, transparency and context. We conclude that this scoping review provides a rigorous basis upon which a generalizable quantitative evaluation framework can be developed.